Hemangioendothelioma of the Spleen - Carriquiry, Luis A; La Piedra, Eduardo; Visca, Pedro; Touya, Eduardo (Cirugía del Uruguay, 1980)
A rare case of hemangio endothelioma of the spleen is reported, His rare frecuency even among the low rate of the spleen's primitive tumors is pointed out. The difficulty of preoperatory diagnosis in spite of scintigrafy and arteriography and the out standing of splenectomy diagnostic and therapeutic at once are signaled. The splenectomy is indicated to prevent complications: splenic rupture, hypersplenism and malignant transformations.